Understanding the antecedents of employee sustainability behaviours: measuring and theorising self- and collective efficacy for sustainability - Ferry, Andrea Joy (Research of GSB, 2018)
Organisations are increasingly committing to ambitious new environmental and social sustainability goals that will necessitate employees across the organisation changing their workplace behaviours. While both practitioners and scholars recognise the benefit of integrating sustainability into everyday work, we have less of an understanding about the antecedents of employees' sustainability behaviours. The psychological literature identifies efficacy - the perception of one's own ability (self-efficacy) and one's group's ability (collective efficacy) to complete a task successfully - as a measurable predictor of behaviour. It also empirically identifies efficacy builders and theorises judgements that give rise to efficacy. Yet, efficacy (at least that which is strongly predictive of behaviours) is task specific and we lack constructs for self- and collective efficacy for sustainability (SES and CES), and their corresponding measures. We also lack an empirically grounded understanding of the judgements that give rise to an individual's SES and CES. This results in two questions: 1) How do we define and measure SES and CES, and 2) what are the judgement factors that lead to SES and CES? To address the first question, I defined these constructs and developed and refined two scales (one each for SES and CES). I undertook preliminary item testing and refinement, assessed scale reliability and validity (Cronbach's alphas of 0.926 for SES and 0.941 for CES), and established construct, convergent and divergent validity through two rounds of testing with acceptably-sized samples. I then trialled the scales in a live corporate environment (Finco) with 781 respondents, further establishing face validity and practical workability. I also conducted a smaller test with MBA students (n=72) to collect qualitative data related to the scales' items. The result is an abbreviated five-item version and a full nine-item version of each of the SES and CES scales, accompanied by implementation guidance. To address the second question, I analysed the qualitative data collected during the scale trialling, as well as data from twelve interviews with Finco and MBA survey respondents. This resulted in a model highlighting eight judgement factors that give rise to SES and four for CES. I thus offer a scholarly and practically relevant set of constructs, measures, and antecedents to assess and enhance employees' efficacy for sustainability behaviours.